Impact Of Polypharmacy On Oral And Dental Health In Geriatric Patients: A Pharmacological Perspective (The Review of Diabetic Studies, 2024)
Background: Polypharmacy is increasingly prevalent among geriatric populations due to the coexistence of multiple chronic diseases. While its systemic consequences are well documented, the impact of polypharmacy on oral and dental health remains underrecognized in clinical practice. Many commonly prescribed medications in older adults exert adverse effects on salivary flow, oral mucosa, periodontal tissues, and bone metabolism, thereby increasing the risk of oral disease and complicating dental management.Objective: This review aims to critically examine the impact of polypharmacy on oral and dental health in geriatric patients from a pharmacological perspective, emphasizing clinically relevant drug-induced oral conditions and the need for interdisciplinary collaboration between pharmacists and dental professionals.Methods: A narrative literature review was conducted using major electronic databases, including PubMed, Scopus, and Web of Science. Relevant studies addressing polypharmacy, drug-induced oral adverse effects, and geriatric dental health were identified, analyzed, and synthesized to provide an integrated overview of pharmacological mechanisms and clinical implications.Results: Evidence indicates that polypharmacy contributes significantly to xerostomia, dental caries, periodontal disease, oral mucosal lesions, and medication-related osteonecrosis of the jaw. Drug classes frequently implicated include antihypertensives, antidepressants, anticholinergics, antidiabetic agents, and antiresorptive therapies. These adverse effects compromise oral function, nutrition, and quality of life, while also increasing the complexity of dental treatment planning.Conclusion: Polypharmacy represents a major yet modifiable risk factor for poor oral and dental health in geriatric patients. Integrating pharmacological assessment into dental care and fostering pharmacist–dentist collaboration are essential to improve clinical outcomes and support healthy aging.